PRODUK GADAI EMAS DI PERBANKAN SYARIAH: ANALISIS MASLAHAH EKONOMI - muhammad yafiz (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
Gold Pawn practices in Islamic Banking can give rise to speculation action due to volatility in the market price of gold. The purpose of this study was to perform stress testing whether there is a bank and the customer losses when the price of gold down by using a static simulation. The data used is secondary data that the value of (qardh) cumulative gold on Islamic banking in Indonesia started March 2004 to May 2015 year. The results of stress testing on the static simulation result of a 50% decline in gold prices shows that there are positions CAR below 8% for 3 months. Practice gold pawn is not in accordance with maslahah mursalah for having violated the rules of economic harm to banks and customers and can be considered to maslahah mulgha or maslahah sukuti where maslahah is not in accordance with personality in the economic analysis of Islam.